A FAST PROCEDURE AS AN ACCESS TO JUSTICE IN ORDER TO REALIZE A SIMPLE, FAST, AND LOW COST PRINCIPLE IN INDONESIA - Afriana, Anita; Fakhirah, Efa Laela (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Civil disputes resolution in court has complicated procedures. For the parties with small value of claims, the settlement through the court with a convoluted procedure is not an appropriate choice because time spent in the court is not comparable to the value of the dispute. On theÂ other hand, the settlement by arbitration and alternative dispute resolution sometimes considered insufficient to provide legal certainty. The objective of this article is to analyze fast procedures that are used in the settlement of a lawsuit simply as a means of access to justice, and the prospects of fast procedures in the civil judicial system of Indonesia. The approach used is normative juridical. The results shows that the regulation of fast procedures in indonesia is an advancement as a means of access to justice but it still required socialization to the public about fast procedure and simple lawsuit.Keywords : Â Access To Justice, Fast Procedures, Simple Lawsuit, Â Private Dispute